Cloning, Sequencing, and Expression of the Pyruvate Carboxylase Gene in Lactococcus lactis subsp. lactis C2 - Wang, H. (American Society for Microbiology, 2000)
A functional pyc gene was isolated from Lactococcus lactis subsp. lactis C2 and was found to complement a Pyc defect in L. lactis KB4. The deduced lactococcal Pyc protein was highly homologous to Pyc sequences of other bacteria. The pyc gene was also detected in Lactococcus lactis subsp. cremoris and L. lactis subsp. lactis bv. diacetylactis strains.